TEACHING MODEL WITH THEME AND RHEME IN SPEAKING SKILL FOR JUNIOR HIGH SCHOOL STUDENTS - Juliansyah Ian (Universitas Majalengka, 2017)
This research is the development of the learning model or models of learning. The learning model developed in this study is the Speech Learning Model in English for Junior High School Students. The purpose of this study was to show that the teaching of English for speaking skill need revising with new model of teaching and learning.The study was conducted by using a qualitative research approach and the application of the methodology of research and development consisting of stages, namely: 1) A preliminary study, 2) Preparation of Model, 3) The First Test of the Model , 4) Revise and Improve the Model, 5) The Second Test of the Model, and 6) Final Model. The study involved students, principals, and teachers of English in some Junior High Schools. Related teaching practices in this study lasted for seven meetings, including the implementation of the test.The result of this study is a model or English language teaching materials focused on increasing the ability to speak or speaking skills. Modules or teaching material resulted from this study contains simple dialogue as well as simple monologue packed in instructions or commands that facilitate learners to speak, starting from the ability to speak in the simplest form of the pronunciation of a word appropriately, submission of ideas in a sentence with proper intonation, responding to a dialogue, conveying a simple description smoothly. This model of learning speaking skills was developed based on the concept of Theme and Rheme.Keywords: Model learning, speech, student, Rheme, theme